Effects of salinity on growth, survival, tissue structure, osmoregulation, metabolism, and antioxidant capacity of Eleutheronema tetradactylum (Shaw, 1804) - Chen, Zongfa; Liu, Weibin; Zheng, Anna; Jin, Minxuan; Huang, Shunmei; Zhao, Lijuan; Tang, Shengliang; Moses Mkulo, Evodia; Wang, Linjuan; Zhang, Huijuan; Lu, Jingheng; Mwemi, Happiness Moses; et al. (Frontiers in Marine Science, 2025)
IntroductionThis study investigates the effects of salinity on the growth, survival, tissue morphology, osmotic regulation, metabolism, and antioxidant responses of juvenile Eleutheronema tetradactylum.MethodsThe experiment was conducted under controlled aquaculture conditions with eight salinity treatments (0, 5, 10, 15, 20, 25, 30, and 35 PSU), each with three replicates (20 fish per replicate) in cylindrical tanks (500 L). Juveniles (mean total length: 16.43 ± 0.87 cm; mean body weight: 35.71 ± 1.067g) were exposed to the treatments for 30 days. Key measurements included plasma osmotic pressure, ion concentrations, and Na+/K+-ATPase (NKA) in the gills, assessed at 0, 1, 10, 20, and 30 days.ResultsSurvival rates, growth parameters, and histopathological changes in gill, intestinal, and kidney tissues were also evaluated. Additionally, plasma levels of lactic acid (LD), triglycerides (TG), glucose (GLU), total superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), total antioxidant capacity (T-AOC), and malondialdehyde (MDA) were measured. The results revealed that survival rates were significantly lower in the 0 PSU group compared to all other salinities (P< 0.05). Growth performance, including specific growth rate (SGR), weight gain rate (WGR), and daily weight gain (DWG), was significantly reduced at high salinities (30 and 35 PSU) (P< 0.05). Histopathological alterations were observed in the gills, intestine, and kidneys, particularly in osmoregulatory tissues. Salinity also significantly affected NKA, plasma osmotic pressure, and ion concentrations. The isosmotic point for E. tetradactylum was determined to be approximately 10.88 PSU. Metabolic responses, including LD, TG, and GLU, exhibited a pattern of initial decline followed by an increase with increasing salinity. SOD activity was significantly higher in the 10 PSU group compared to the 30 and 35 PSU groups (P< 0.05), while T-AOC showed a “U”-shaped response to increasing salinity. GSH-Px activity decreased with salinity, especially at 35 PSU (P< 0.05), while MDA levels did not vary significantly (P > 0.05).DiscussionIn conclusion, E. tetradactylum belongs to euryhaline fish species, with optimal growth occurring at lower salinities(5-10PSU). High salinity (30–35 PSU) adversely affects growth and antioxidant defense mechanisms, highlighting the species’ sensitivity to elevated salinity. Beyond identifying species-specific sensitivity, this work provides actionable guidelines for optimizing aquaculture practices, reducing metabolic costs, and mitigating oxidative stress in captive-reared populations.